Excitonic Transport and Intervalley Scattering Dynamics in Large‐Size Exfoliated MoSe2 Monolayer Investigated by Heterodyned Transient Grating Spectroscopy. Issue 12 (16th November 2020) - Kuhn, Henning; Wagner, Julian; Han, Shuangping; Bernhardt, Robin; Gao, Yan; Xiao, Liantuan; Zhu, Jingyi; van Loosdrecht, Paul H. M.
Abstract: Exciton intervalley scattering, annihilation, relaxation dynamics, and diffusive transport in monolayer transition metal dichalcogenides are central to the functionality of devices based on them. Here, these properties in a large‐size exfoliated high‐quality monolayer MoSe2 are addressed directly using heterodyned transient grating spectroscopy at room temperature. While the free exciton population is found to be long‐lived (≈230 ps), an extremely fast intervalley scattering (≤170 fs) is observed, leading to a negligible valley polarization, consistent with steady state photoluminescence measurements and theoretical calculation. The exciton population decay shows an appreciable contribution from the exciton–exciton annihilation, with an annihilation rate of ≈0.01 cm 2  s −1 . The annihilation process also leads to a significant distortion of the transient grating evolution. Taking this distortion into account, consistent exciton diffusion constants D  ≈ 1.4 cm 2  s −1 are found by a model simulation in the excitation density range of 10 11 –10 12  cm −2 . The presented results highlight the importance of correctly considering the many‐body annihilation processes to obtain a pronounced understanding of the excitonic properties of monolayer transition metal dichalcogenides. Abstract : Exciton–exciton annihilation effect to both population and grating dynamics have been solved in exfoliated monolayer MoSe2 . Extremely fast intervalley scattering dynamics and much longer population lifetime of excitons are identified.